Analisis Quiet-Quitting pada Dosen PTN Universitas Teuku Umar - Rosa br Tarigan, Via Dolo (Teewan Journal Solutions, 2025)
This study aims to test and analyze the direct effect of leadership empowerment on job satisfaction and job satisfaction on quitting intention, as well as the indirect effect of leadership empowerment on quitting intention through job satisfaction on lecturers at Teuku Umar University State Universities. This study applies a quantitative approach and uses a cross-sectional survey technique. Multistage random sampling is used for gradual sampling. Of the 443 active lecturers, 141 respondents were selected using the protocop of power analysis formula. SmartPLS was used to test the data. The results of this study indicate that: 1) leadership empowerment has a positive and significant effect with a t-statistic value of 4.870 2) job satisfaction can mediate a significant and positive effect on quitting intention with a t-statistic value of 4.870 and 3) leadership empowerment has a positive and significant effect on quitting intention through job satisfaction with a t-statistic value of 2.397 on Lecturers at Teuku Umar University State Universities